MANAGERIAL ACCOUNTING AND ITS IMPORTANCE FOR THE FUTURE MANAGEMENT OF THE COMPANY - Ponisciakova, Olga (Doprava a spoje, 2012)
Traditional approaches to gather information necessary for management in recent years seem to be insufficient and the financial accounting in particular, has more ore less memorandum character. Information-oriented to history is sufficient only to a certain extent, turbulent environment raises the requirements for most accurate prediction of future. Ambition to reply such requests has managerial accounting, discussed in this article.